Fasudil Ameliorates Methotrexate-Induced Hepatotoxicity by Modulation of Redox-Sensitive Signals - Esam M. Aboubakr; Ahmed R. N. Ibrahim; Fares E. M. Ali; Ahmed A. E. Mourad; Adel M. Ahmad; Amal Hofni (MDPI AG, 2022)
Methotrexate (MTX) is one of the most widely used cytotoxic chemotherapeutic agents, and it is used in the treatment of different autoimmune disorders. However, the clinical applications of MTX are limited by its hepatic toxicity. Hence, the present study was conducted to evaluate the efficacy of fasudil (Rho-Kinase inhibitor) in the amelioration of MTX hepatotoxicity and the possible underlying mechanisms. Experimentally, 32 male Sprague Dawley rats were used and divided into four groups: control, MTX (20 mg/kg, i.p., single dose), fasudil (10 mg/kg/day i.p.) for one week, and fasudil plus MTX. It was found that MTX significantly induced hepatitis and hepatocellular damage, as shown by abnormal histological findings and liver dysfunction (ALT and AST), with up-regulation of the inflammatory mediators NF-κB-p65 and IL-1β. Moreover, MTX remarkably disrupted oxidant/antioxidant status, as evidenced by malondialdehyde (MDA) up-regulation associated with the depletion of superoxide dismutase (SOD), catalase, and reduced glutathione (GSH) levels. Moreover, MTX reduced the hepatic expression of B-cell lymphoma 2 (Bcl-2). On the contrary, the i.p. administration of fasudil significantly ameliorated MTX hepatotoxicity by histopathological improvement, restoring oxidant/antioxidant balance, preventing hepatic inflammation, and improving the hepatic anti-apoptotic capability. Furthermore, fasudil hepatic concentration was determined for the first time using the validated RP-HPLC method. In conclusion, the present study revealed that fasudil has a reliable hepatoprotective effect against MTX hepatotoxicity with underlying antioxidant, anti-inflammatory, and anti-apoptotic mechanisms. It also introduced a new method for the determination of fasudil hepatic tissue concentration using the RP-HPLC technique.